Parental sport achievement and the development of athlete expertise - Wilson, S. G.; Wilson, M. J.; Baker, J. (European Journal of Sport Science, 2019)
This study sought to examine how parental sport involvement and attainment were related to the eventual level of competitive sport attained by their children. Athletes (n = 229) were divided into three skill level groups (elite: n = 139; pre-elite: n = 33; non-elite: n = 57), based on the peak competition level achieved in their career, which were compared using chi-squares tests of independence and analyses of variance according to parents sport characteristics provided through the Developmental History of Athletes Questionnaire. Parental recreational and competitive sport participation was overrepresented among elite athletes, as were parents who reached an elite level of sport themselves. Results were found to differ according to parent sex, with athlete skill level significantly related to the sport participation and skill level of fathers, but not mothers. Results suggest parental sport experiences at different levels of competition influence the development of athletes, although these relationships are subject to many factors.